Konsep Pendidikan Akhlak dalam Perspektif Kitab Bidayatul Hidayah: Pendekatan dan Relevansinya dalam Konteks Pesantren Era Modern - Nina Ransi; Muhammad Shohib (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the concept and educational approaches of moral education presented in Bidayatul Hidayah written by Abu Hamid Muhammad Al-Ghazali and examine its relevance to Islamic boarding school education in the modern era. This research employs a qualitative approach with a library research design. The primary data source is Bidayatul Hidayah, while secondary sources include books, journal articles, and other relevant literature discussing moral education and Islamic boarding school systems. Data were analyzed using content analysis to identify the core concepts and educational approaches embedded in the text. The findings reveal that the concept of moral education in Bidayatul Hidayah consists of three main dimensions: obedience to God, avoiding both outward and inward sins, and maintaining proper social ethics in human interactions. The educational approaches identified include religious-spiritual orientation, habituation, role modeling, and preventive–repressive methods. These concepts remain relevant for contemporary pesantren as they provide a strong moral framework for students facing modern challenges such as digitalization and moral degradation. When implemented adaptively, Al-Ghazali’s ideas can strengthen the role of pesantren in shaping morally upright and socially responsible generations